Influence of Capital, Labor and Wage Levels on Production of Super Tofu Padang - Riani Sutra; Febryandhie Ananda (Basic and Applied Accounting Research Journal, 2021)
The purpose of this study was to determine the effect of capital, labor, and wage levels on company production. The research method uses quantitative descriptive with 36 samples from January 2016 until December 2018. Based on the partial t test it can be concluded that capital has a negative and significant effect on production. Based on the partial t test it can be concluded that the variable of labor does not affect production. Based on the partial t test it can be concluded that the wage level variable has positive and significant effect on production. Based on the simultaneous F test it can be said that capital, labor, and wage levels together affect production. The ability of the independent variable in explaining the dependent variable was 77.40%, while the remaining 22.60% was influenced by other variables apart from the variables studied